SENTIMENT ANALYSIS OF ICT SERVICE USER USING NAIVE BAYES CLASSIFIER AND SVM METHODS WITH TF-IDF TEXT WEIGHTING - Trisnawati, Wulan; Wibowo, Arief (Informatika, Universitas Jenderal Soedirman, 2024)
Pusintek is one of the government units in Indonesia responsible for managing Information and Communication Technology (ICT), providing various ICT services to users in central and regional offices through the ICT Service Catalog. The level of service fulfillment in Pusintek's IT Service Catalog significantly influences the effectiveness and efficiency in meeting service agreements, providing accurate information, and handling disruptions promptly. User satisfaction is measured through surveys to plan improvements to ICT services, but there is currently no method to classify sentiment from survey comment data. This research aims to classify sentiment and understand customer opinions and satisfaction trends regarding ICT services. The study applies the Naïve Bayes Classifier and Support Vector Machine (SVM) methods to classify positive and negative comments in user satisfaction surveys of ICT services. The data used consists of comments from the 2022 ICT user satisfaction survey results. Based on the test results, it is observed that the SVM algorithm provides higher accuracy compared to the Naïve Bayes algorithm. Utilizing the existing dataset with established opinion values, classification modeling using Naïve Bayes Classifier and Support Vector Machine (SVM) proves capable of classifying ICT user sentiment into 3 sentiment classes: Positive, Neutral, and Negative. From the data above, it is concluded that the SVM algorithm achieves the highest accuracy of 88.76%, highest precision of 89.68%, recall of 88.76%, and an f1-score of 89.12%.